Analisis Pengaruh Kebijakan Dividen, Leverage, dan Profitabilitas Terhadap Nilai Perusahaan pada Perusahaan Sub Sektor Konstruksi Dan Bangunan yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020 - Anisa Fitria Dhovairy (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This study examines the effect of dividend policy, leverage, and profitability on firm value simultaneously and partially in construction and building sub-sector companies listed on the Indonesia Stock Exchange from 2016-to 2020. In contrast to previous studies, this study measures the dividend policy variable with DPR, leverage with DER and DAR, and profitability with ROE. It uses Tobin's Q ratio for the firm value variable. This study uses a quantitative approach. The number of samples in this study is 6 companies from 23 construction and building sub-sector companies in 5 years using the purposive sampling method. Processing research data using multiple linear regression analysis techniques assisted the SPSS 25 program. This study shows that the DPR and DAR have a negative and insignificant effect on firm value (Tobin's Q). DER and ROE have a positive and significant impact on firm value. The construction and building companies are suggested to regard factors that increase the company's value for the shareholders' welfare